A comparative study of additively manufactured thin wall and block structure with Al-6.3% Cu alloy using cold metal transfer process - Cong, Baoqiang; Qi, Zewu; Qi, Bojin; Sun, Hongye; Zhao, Gang; Ding, Jialuo (MDPI, 2017)
In order to build a better understanding of the relationship between depositing mode and porosity, microstructure, and properties in wire + arc additive manufacturing (WAAM) 2319-Al components, several Al-6.3%Cu deposits were produced by WAAM technique with cold metal transfer (CMT) variants, pulsed CMT (CMT-P) and advanced CMT (CMT-ADV). Thin walls and blocks were selected as the depositing paths to make WAAM samples. Porosity, microstructure and micro hardness of these WAAM samples were investigated. Compared with CMT-P and thin wall mode, CMT-ADV and block process can effectively reduce the pores in WAAM aluminum alloy. The microstructure varied with different depositing paths and CMT variants. The micro hardness value of thin wall samples was around 75 HV from the bottom to the middle, and gradually decreased toward the top. Meanwhile, the micro hardness value ranged around 72–77 HV, and varied periodically in block samples. The variation in micro hardness is consistent with standard microstructure characteristics.
Keywords: wire + arc additive manufacturing; aluminum alloy; cold metal transfer; depositing path; porosity; microstructure; micro hardness